2019
DOI: 10.1152/ajpheart.00456.2018
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen determines sex differences in adrenergic vessel tone by regulation of endothelial β-adrenoceptor expression

Abstract: Vessels of female rats constrict less and relax more to adrenergic stimulation than vessels of males. Although we have reported that these sex-specific differences rely on endothelial β-adrenoceptors, the role of sex hormones in β-adrenoceptor expression and related vessel tone regulation is unknown. We investigated the role of estrogen, progesterone and testosterone on β-adrenoceptor expression and adrenergic vessel tone regulation, along with sex-specific differences in human mammary arteries. The sex-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
(59 reference statements)
2
31
0
Order By: Relevance
“…) and have greater beta‐adrenergic sensitivity as a result of oestrogen‐dependent increases in beta‐adrenoceptor expression (Riedel et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…) and have greater beta‐adrenergic sensitivity as a result of oestrogen‐dependent increases in beta‐adrenoceptor expression (Riedel et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Participants underwent a single night of sleep with nocturnal pulse oximetry (WristOx2, Model 3150; Nonin, Plymouth, MN, USA) and were excluded if they had indications of undiagnosed sleep apnoea, defined as an oxygen desaturation index ࣙ5 events h -1 (based on a desaturation ࣙ 4%; nVision, version 6.4; Nonin). Finally, only male participants were enrolled because women have a lower probability of developing OSA (Peppard et al 2013), are less sensitive to alpha-adrenergic stimulation (both alpha 1 and 2) (Schmitt et al 2010) and have greater beta-adrenergic sensitivity as a result of oestrogen-dependent increases in beta-adrenoceptor expression (Riedel et al 2019).…”
Section: Study Participantsmentioning
confidence: 99%
“…Symbols represent mean ± SEM for n of 6 in each experimental group. Asterisk (*) indicates a significant effect of PKI on responses; Δ indicates a significant effect of nadolol on responses in the presence of PKI (P < .05, two-way ANOVA with Sidak's post hoc comparison) et al, 2001), although reported pEC 50 values for arterial relaxation are around 5 (Brawley et al, 2000;Flacco et al, 2013;Riedel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We do not know why the effect of ageing differs between men and women, but some insights can be gleaned from prior work. Examination of rat mesenteric arteries and human mammary arteries indicated that oestrogen augments β‐adrenergic endothelial receptor expression in females, resulting in greater isoprenaline‐induced vasodilatation through nitric oxide signalling in comparison to males (Riedel et al., 2019). We previously discovered that nitric oxide synthase is a major player in mediating β‐adrenergic cutaneous vasodilatation in young men (Fujii et al., 2017c).…”
Section: Discussionmentioning
confidence: 99%
“…This was evidenced by the following findings: (i) ageing had no effect on the magnitude of prostacyclin‐mediated cutaneous vasodilatation in men (Fujii, Notley, Minson, & Kenny, 2016b), whereas it augmented this vasodilatation in women (Fujii, McNeely, Nishiyasu, & Kenny, 2017d); (ii) ageing attenuated ATP‐mediated cutaneous vasodilatation in men (Fujii et al., 2018), but augmented this vasodilatation in women (Fujii et al., 2019b); and (iii) ageing attenuated low‐to‐moderate levels of muscarinic‐mediated sweating in men, whereas reductions were only observed at high levels of muscarinic‐mediated sweating in women (Fujii et al., 2019a). Furthermore, oestrogen is thought to be an important modulator of β‐adrenergic receptor expression in women, which might underlie sex‐dependent differences in cutaneous end‐organ responses to β‐adrenergic agonists (Riedel et al., 2019). Taken together, it is therefore plausible that the effects of ageing on β‐adrenergic cutaneous vasodilatation and sweating, if any, might also be modulated by sex.…”
Section: Introductionmentioning
confidence: 99%